The Effectiveness of Education on Prevention of Osteoporosis among High School Female Students - S Nejati; N Rasoulzadeh; A Sedighiyani (Tehran University of Medical Sciences, 2009)
Background & Aim: Osteoporosis is a silent and preventable disease that mostly affects women. Osteoporosis prevention requires enhancing knowledge and awareness of students. The purpose of this study was to assess the effectiveness of education on prevention of osteoporosis among high school female students in the sixth distinct of Tehran. Methods & Materials: In this randomized controlled trial, 600 students were selected using cluster sampling method. Data were gathered using a three-part questionnaire including demographic, knowledge, and practice items. After the baseline measurement, the students were randomly allocated into intervention and control groups. Two educational sessions were held for the intervention group. At the end of the sessions, educational booklets were distributed among the students. The educational strategies included giving lectures, and practicing physical exercises. After two weeks, the participants completed the questionnaires again. The educational classes were held for the control group after the last measurements. Results: Data analysis showed that the mean of knowledge score and the participants;apos practice were significantly different between two groups after the intervention (P<0.001). Conclusion: Regarding the effect of education on enhancing students;apos awareness and practice about osteoporosis prevention, designing educational programs could be beneficial.